"Manibus, oh …": Virgil's loving hands - Mussio, Thomas E (Spunti e Ricerche, 2016)
Dante's only direct citation of Virgil's Latin occurs in Purgatorio 30, when he has angels sing to honor the coming of Beatrice. This re-contextualization of Virgil's words allows that even if he is excluded from heaven, his poetry has a place there. Yet this citation of Virgil is significant in another way: even as it recognizes the poignancy of Virgil's tragedy, it marks the beginning of the climax in Purgatorio of Dante's efforts to understand Virgil's role in his healing.